Das Gesetz über den Verkauf von Finanzprodukten - Schulte, Christine (Zeitschrift für Japanisches Recht, 2005)
While reform of the financial system has been high on the political agenda in Japan since the 1990s, consumer protection – and in the field of financial services, investor protection – have not. The Financial Products Sales Law of 2001 has, however, opened the way for a standardized treatment of losses incurred by private investors through a lack of explanation of risks on the part of the financial services industry. The Financial Products Sales Law takes most of its cues from a series of trials about liability for losses incurred by private investors in the 1990s. “Loss” is defined in terms of the original sum invested; if the amount the investor receives after termination of the contract is smaller than the amount originally invested, the investor is seen to have incurred a loss. The law introduces a concept of strict liability. Institutions that offer financial products must inform potential purchasers about certain risks inherent in the product or the investing process that might lead to losses. If they fail to inform the investor about these risks, or if the information is faulty, they are held liable for losses. On the other hand, any losses incurred by an investor who has been informed about product risks according to the standards stipulated by the law are his or her own responsibility. The law also makes provisions for exceptional cases in which information need not be provided and seeks to establish a selfcontrol system for providers of financial services. Although a number of smaller questions remain to be clarified, the law shows a marked change in the way consumers-as-investors are seen by the financial bureaucracy and by lawmakers. In theory, the transition from supplicants at the bidding of a powerful financial industry to well-informed individuals that can deal with providers of financial services on an equal basis is quite stunning; it remains to be seen how the financial bureaucracy, the financial services industry and last but not least consumers-as-investors live up to the challenge.